2014
DOI: 10.1371/journal.pone.0106517
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Outcomes of Anticoagulant Use among Hospitalized Patients with Chronic Kidney Disease: A Comparison of the Rates of Major Bleeding Events between Unfractionated Heparin and Enoxaparin

Abstract: BackgroundAnticoagulation therapy is usually required in patients with chronic kidney disease (CKD) for treatment or prevention of thromboembolic diseases. However, this benefit could easily be offset by the risk of bleeding.ObjectivesTo determine the incidence of adverse outcomes of anticoagulants in hospitalized patients with CKD, and to compare the rates of major bleeding events between the unfractionated heparin (UFH) and enoxaparin users.MethodsOne year prospective observational study was conducted in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 27 publications
1
18
1
Order By: Relevance
“…The study identified the incidence of major bleeding events from therapy with full-therapeutic doses of UFH, or with adjusted enoxaparin (1 mg/kg once daily), and compared the rates of major bleeding between the UFH and enoxaparin users. In this study, major bleeding occurred in 1 in 3 patients who received anticoagulation during hospital stay (hazard ratio /mL; P < 0.001) [35]. In the above mentioned studies, the risk of bleeding complication was higher with fulltherapeutic doses of UFH compared to enoxaparin.…”
Section: Clinical Practicementioning
confidence: 48%
See 1 more Smart Citation
“…The study identified the incidence of major bleeding events from therapy with full-therapeutic doses of UFH, or with adjusted enoxaparin (1 mg/kg once daily), and compared the rates of major bleeding between the UFH and enoxaparin users. In this study, major bleeding occurred in 1 in 3 patients who received anticoagulation during hospital stay (hazard ratio /mL; P < 0.001) [35]. In the above mentioned studies, the risk of bleeding complication was higher with fulltherapeutic doses of UFH compared to enoxaparin.…”
Section: Clinical Practicementioning
confidence: 48%
“…For example, in a retrospective observational study of 7721 dialysis patients who received thrombophylaxis therapy with either UFH or enoxaparin, reported that enoxaparin was not associated with higher bleeding risk in comparison with UFH (risk ratio, 0.98; 95 % CI 0.78-1.23), concluding that thrombophylaxis doses of enoxaparin appeared to be safe and could be used as an alternative to UFH in dialysis patients [42]. More recently, in a prospective study for the treatment of thromboembolic events in hospitalized patients with CKD from stages 3-5, enoxaparin administrated in adjusted therapeutic doses was associated with lower bleeding events compared to UFH [35]. The results of the study highlighted the safety of enoxaparin when administered in therapeutic doses with dose adjustment for patients with severe CKD.…”
Section: Clinical Practicementioning
confidence: 99%
“…Sharif-Askari et al compared patients with CKD stages 3-5 and noted a higher incidence of major bleeding with enoxaparin over UFH (HR4.79). 24 Thorevska and colleagues also reported an increased incidence of bleeding (2.54x) with therapeutic enoxaparin as compared to UFH 25 in patients with GFR < 60 mL/min. Levine et al showed a positive relationship between anti-factor Xa level and incidence of wound hematoma in hip replacement patients with once-daily prophylactic enoxaparin, 26 whereas Sanderlink et al showed that, after 5 days of enoxaparin prophylaxis, anti-factor Xa levels were found to be unrelated to renal function until CrCl < 20 mL/ min.…”
Section: Discussionmentioning
confidence: 94%
“…(10). Furthermore, since renal excretion is the main elimination route for enoxaparin, dose adjustment is required in patients with renal dysfunction, indicated by creatinine clearance of less than 30 ml/min (6,11). An assessment of the monitoring procedure revealed that anti Xa factor, and stool occult blood test were not measured for any of the patients included in this study indicating that the physicians did not consider these tests as part of the monitoring procedure.…”
Section: Discussionmentioning
confidence: 99%
“…It is the leading LMWH with the largest volume of published information on use in the setting of percutaneous coronary intervention (4) and the most widely studied LMWH for the prophylaxis/treatment of venous thromboembolism (VTE) (5). The ease of administration and the predictable anticoagulant effect of enoxaparin which eliminate the need for routine laboratory monitoring (4,(6)(7), relatively low cost and its wide availability (4) have led to wide applicability and general acceptability of the drug for the prophylaxis/treatment of thromboembolic disorders in most healthcare settings worldwide. Hence, it is a suitable candidate for DUE study.…”
Section: Introductionmentioning
confidence: 99%